Professional Development for Vocational High School Teachers through Incremental Teacher Competence Standards - Waluyanti, Sri; Santoso, Djoko; Munir, Muh; Wulandari, Bekti; Raduan, Atiqah (Jurnal Pendidikan Teknologi dan Kejuruan, 2018)
This study presents the competence of vocational high school teachers through the implementation of five work dimensions of teachers’ incremental standard competence. It was conducted in the framework of the sustainable professional development for vocational teachers using participatory action research at two Vocational High Schools by involving 50 teachers. The study included socialization of incremental competency standards and reflection, mentoring and consultation sessions, and teaching reports and reflection. Data collection used observation, assessment, and teaching reports. To optimize the results, it was ended with a focus group discussion involving the Institute for Education Quality Assurance. The results showed that the teachers’ competence in the aspects of the learning plan, learning resource utilization, media utilization, facilitating students’ learning needs, ability to create learning evaluation instrument, and following up the learning outcomes were all categorized as good while the aspect of developing students’ potentials both curriculum implementation and reflection ability was categorized as very good. It indicates the mentoring and the consultation worked effectively. Meanwhile, the teachers’ ability that should be improved is the creation of assessment instruments.